Intraocular pressure reduction in patients treated with micropulse laser trabeculoplasty vs selective laser trabeculoplasty - Irina Ariza Torrado; Claudia Johanna Martínez Córdoba; Sara Edith Moreno Mazo; Jeanneth Eloyne Toquica; Patricia Hernandez (Indian Journal of Ophthalmology)
Purpose: To compare intraocular pressure (IOP) reduction achieved in patients treated with two different laser trabeculoplasty technologies over a 6-month follow-up period. Design: This was a quasi-experimental, interventional study. Methods: Patients with indications for laser trabeculoplasty were included. One eye of each patient was randomly assigned to receive selective laser trabeculoplasty (SLT), while the other received micropulse laser trabeculoplasty (MLT). A glaucoma specialist monitored each patient for 6 months. IOP data were recorded at 1, 3, and 6 months post-intervention. Results: A total of 296 eyes from 148 patients were analyzed. Indications for trabeculoplasty were primary open-angle glaucoma in 93 patients (62.8%), ocular hypertension in 28 (18.9%), primary angle-closure glaucoma in 24 (16.2%), and pigmentary glaucoma in 3 (2.0%). No significant difference in IOP reduction was observed between the two groups. The mean IOP reduction was 2.77 mmHg (17.3%) and 2.81 mmHg (17.5%) in the MLT and SLT groups, respectively. Both groups showed significant differences between baseline and final IOP. The mean baseline IOP was 16.1 mmHg and 16.0 mmHg, and the final IOP was 13.3 mmHg and 13.2 mmHg for the MLT and SLT groups, respectively. No treatment-related complications were reported, and no significant differences in the need for re-treatment or filtering surgery were observed. Conclusions: Laser trabeculoplasty is an effective treatment for glaucoma and/or ocular hypertension. IOP reduction was comparable between MLT and SLT, with no significant differences between the two technologies. Their favorable safety profile makes them an excellent choice as either a first-line or adjuvant treatment for IOP control.